Perlindungan Hukum Konsumen: Efektivitas Pengawasan Produksi Air Minum Isi Ulang - Arfanita Arfanita; Insarullah Insarullah; Andi Nurul Isnawidiawinarti Achmad (Amanna Gappa, 2022)
This study aims to determine the effectiveness of supervision of the production of refilled drinking water and the role of the Consumer Dispute Settlement Agency in providing legal protection to consumers in Palu City. This study uses empirical legal research on the operation of law (law in action) in society. The results show that legal protection for consumers of refilled drinking water is the responsibility of local governments. Supervision of refilled drinking water production in Palu City needs to be more adequate than expected by consumers. The public does not fully know the Consumer Dispute Settlement Agency, so since its establishment until this research, there has never been a consumer dispute over refilled drinking water before being tried at the Palu City Consumer Dispute Settlement Agency. Therefore, it is necessary to provide guidance and outreach to the community regarding the feasibility of refilling drinking water and the institutional existence of the Consumer Dispute Settlement Agency.